Exploration of the Perceived Value of Self-Leadership Capacity in Physical Therapist Clinicians. - Harrison, Diana A.; Santurri, Laura; Borrero, Lisa; Green-Wilson, Jennifer (Physiotherapy Canada, 2026)
Purpose: Self-leadership, or leading oneself, is a critical component of leadership linked to improved individual performance, team effectiveness, and patient and organizational outcomes. This qualitative study explores physical therapist clinicians' perceived value of self-leadership in their clinical practice and their interactions with inter-professional team members. Method: Purposeful sampling was used to recruit participants via the maximum variation strategy. Eleven licensed physical therapist clinicians with 2–39 years of clinical experience in five different clinical settings participated. Participants engaged in individual, semi-structured interviews that were audio-recorded and transcribed verbatim. Study rigour was addressed through the use of multiple coders, memoing, and member checking. Results: Four main themes emerged: developing expertise, pursuing professional growth, discovering and amplifying voice, and advocacy. The "why" behind the actions of those interviewed was to influence patient outcomes and quality of care and to address role identity as a physical therapist across multiple contexts. Conclusions: This is the first known exploration of the perceived value of self-leadership capacity in physical therapist clinicians. The study results suggest that leadership must be reframed as self-leadership, the precursor to leading others, so physical therapist clinicians can lead at all levels in everyday practice. Lay Summary: The researchers wanted to understand how physical therapists view self-leadership. Self-leadership is basically being good at leading oneself – setting goals, staying motivated, and taking charge of one's professional development. They interviewed 11 physical therapists with 2–39 years of experience working in different health care settings. The physical therapists talked about four areas in which self-leadership mattered the most: building expertise (learning and improving their clinical skills), career growth (looking for new opportunities), finding their voice (gaining confidence to speak up and share ideas), and advocating (making sure that patients receive excellent care and physical therapists are respected). Everything was related to one main goal: providing the best possible patient care while establishing their identity and value as health care professionals. This is the first study to look at self-leadership in physical therapist clinicians. This research is important because it shows that before physical therapists can effectively lead their patients and health care teams, they first need to address leading themselves. The researchers argue that the health care field needs to rethink leadership; instead of just focusing on managing others, the field should start with helping professionals develop strong self-leadership skills.